1981
DOI: 10.1007/bf00219357
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of neurons in the ventromedial nucleus or the hypothalamus in ovariectomized rats with or without estrogen treatment

Abstract: The fine structure of the ventrolateral and dorsomedial subdivisions of the ventromedial nucleus (VMN) of the hypothalamus was examined in ovariectomized/control and ovariectomized/estrogen-treated rats to compare neurons of these areas to other neurons (specifically the ventrolateral thalamus), and to determine the effects of estrogen on these cells. The neurons of the VMN contain a large nucleus with a prominent nucleolus, rough endoplasmic reticulum (RER), polysomes, a Golgi complex, coated, uncoated and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
30
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(34 citation statements)
references
References 34 publications
4
30
0
Order By: Relevance
“…E 2 can modulate dendrite morphogenesis and induce synaptogenesis in hypothalamic (8)(9)(10)(11) and extrahypothalamic neuronal populations (12,13), and such structural plasticity may mediate E 2 feedback effects (14). That the ER␣ isoform appears to mediate many of these effects rapidly (15) is consistent with the idea that membrane-initiated, nonclassical ER␣ signaling can rapidly induce the actin-cytoskeletal reorganization required for synaptic remodeling (16).…”
mentioning
confidence: 60%
See 1 more Smart Citation
“…E 2 can modulate dendrite morphogenesis and induce synaptogenesis in hypothalamic (8)(9)(10)(11) and extrahypothalamic neuronal populations (12,13), and such structural plasticity may mediate E 2 feedback effects (14). That the ER␣ isoform appears to mediate many of these effects rapidly (15) is consistent with the idea that membrane-initiated, nonclassical ER␣ signaling can rapidly induce the actin-cytoskeletal reorganization required for synaptic remodeling (16).…”
mentioning
confidence: 60%
“…Because ER␣ signaling and PAKs can both mediate rapid actin cytoskeletal organization and morphological plasticity (11,23,(48)(49)(50)(51), it is thus possible that these downstream cellular events comprise a major route by which E 2 -activated PAKs may mediate negative feedback control over GnRH and, hence, LH secretion. It remains to be determined whether such a rapid, PAK-mediated alteration in cell connectivity functions in this manner and, if so, which of the many known PAK substrates (e.g., actin-related protein 2/3 complex, filamin, and/or cofilin) (19) may mediate these actions.…”
Section: Discussionmentioning
confidence: 99%
“…The earliest estrogen effect is the increase of transcription of ribosomal RNA, 13 followed rapidly by morphological effects, including those in the nucleolus itself 14 and a striking elaboration of rough endoplasmic reticulum in the cytoplasm. 15 Catherine Woolley 16 and her colleagues have shown, probably consequent to the phenomena above, a stimulatory effect of estrogen treatment on dendritic growth. In the female rat hypothalamus, Maya Frankfurt 17 and Lori Flanagan 18,19 have reported that estrogens foster dendritic growth and an increased number of synapses.…”
mentioning
confidence: 98%
“…Both rat ventromedial nucleus (of unknown steroid receptor content) and the ER-containing VL cells of the guinea-pig contain large stacks of Golgi cisternae, Nissl bodies (stacks of rough endoplasmic reticulum) with ribbon formations, and multivesicular bodies. Since the occurrence of the 'ribbons' and extent of the stacking of the endoplasmic reticulum may be dependent on hormone status in this (35) and other brain regions (c.g. 45), the ER-immunoreactivc neurons of the intact guinea-pig may contain substantially more ribboned rough endoplasmic reticulum than viewed here in our ovariectomized animals.…”
Section: Figmentioning
confidence: 99%